One-Step Loading on Natural Mineral Halloysite Nanotube: An Effective Way to Enhance the Stability of Perovskite CsPbX3 (X = Cl, Br, I) Quantum Dots - Hao, Jiarui; Qu, Xingyu; Qiu, Lei; Li, Guogang; Wei, Yi; Xing, Gongcheng; Wang, Hongquan; Yan, Chunjie; Jang, Ho Seong; Cheng, Ziyong; Lin, Jun (WILEY-V C H VERLAG GMBH, 2019)
Currently, poor luminescence stability seriously impedes the practical application of inorganic halide perovskite (CsPbX3, X = Cl, Br, and I) quantum dots (QDs) in optoelectronic devices. In present work, CsPbX3 QDs are successfully assembled on natural mineral halloysite nanotubes (HNTs) for improving the luminescence performances. Monodispersed CsPbX3 QDs are arranged on two edges of HNTs in a highly ordered manner, which possibly originates from the electrostatic interaction between halogen ion and surface hydroxyl (Sur-OH2+) on the section face of HNTs. As expected, the photoluminescence (PL) performances of CsPbX3@HNTs nanocomposites are obviously improved. The PL intensity still can be maintained even 80% when working at 100 degrees C. Almost no emission degradation is observed after storing in an open ambient condition for 28 days. Moreover, the PL intensity also maintains 82% of room temperature (RT) intensity after continuously being illuminated by 365 nm UV lamps for 144 h. Excellent white light with Commission Internationale de l'Eclairage (CIE) chromaticity coordinates (0.34, 0.32) of the white light-emitting diodes (w-LEDs) fabricated by CsPbBr3@HNTs, CsPbBr1.2Cl1.8@HNTs, and CsPbBr1.2I1.8@HNTs phosphors are achieved. This work opens up a new insight in achieving stable CsPbX3 QD-based multifunctional materials by designing nanocomposites with natural clay mineral.